If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -34 = 46 + 7x Reorder the terms: -34 + 12x = 46 + 7x Solving -34 + 12x = 46 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -34 + 12x + -7x = 46 + 7x + -7x Combine like terms: 12x + -7x = 5x -34 + 5x = 46 + 7x + -7x Combine like terms: 7x + -7x = 0 -34 + 5x = 46 + 0 -34 + 5x = 46 Add '34' to each side of the equation. -34 + 34 + 5x = 46 + 34 Combine like terms: -34 + 34 = 0 0 + 5x = 46 + 34 5x = 46 + 34 Combine like terms: 46 + 34 = 80 5x = 80 Divide each side by '5'. x = 16 Simplifying x = 16
| 12b=.2 | | (6g-9)+1/3(15-9g)= | | 12+3d=d | | 5.7+b=23 | | -4x+82=-86-10x | | 25=n-(3) | | R^2=-96 | | (0.01)(1)+0x=0.02(x+1) | | 24x^2-58x+40=7 | | 2/3y-12 | | 17=-d | | -2=j-3/2 | | 3.2+9.3x=0.2x+1.4 | | -5+6f=5f+2 | | 3/2(5x-4)+1=1/3x-2(x-5) | | -8(x+2)=-3x-31 | | -1/2-7=_ | | 2/8k=16/24 | | 6y-10+6y+10= | | -6g+8=-4g | | 5x-8=6x+15 | | -5t^2-8t=-120 | | -3b+4b=14-b | | 10x+-5=3x+9 | | 13=-3n+11-n | | 1/12x=3 | | 7(5x+3)=371 | | 72=-8u | | 1/2(8x-6)=9 | | 6(5x+7)=102 | | -13=y/2 | | k-9.1=4 |